The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12144-022-02987-2
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety model of cyberchondria, fears, obsessions, sleep quality, and negative affect during COVID-19

Abstract: The aim of the study was to explore the relationships among cyberchondria, fear of COVID-19, health anxiety, obsessions, sleep quality, and negative affect in a national community sample of Turkish participants. A sample of 8,276 volunteers, aged between 18 and 65, were recruited via an online platform. The Perceived Vulnerability about Diseases Questionnaire, Fear of COVID-19 Scale, Cyberchondria Severity Scale, Short Health Anxiety Inventory, Depression Stress Anxiety Scale-21, Obsessive–Compulsive Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 85 publications
(70 reference statements)
2
15
0
Order By: Relevance
“…The respondents are asked to rate the items on a five-point scale and the higher score reflects the higher severity of cyberchondria (McElroy et al, 2019 ). Turkish form of the CSS-12 has original factor structure and good psychometric characteristics (Yalçın et al, 2022 ). The Turkish version of the CSS-12 revealed high internal consistency on the present data with Cronbach’s alphas ranging from 0.72 to 0.89.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respondents are asked to rate the items on a five-point scale and the higher score reflects the higher severity of cyberchondria (McElroy et al, 2019 ). Turkish form of the CSS-12 has original factor structure and good psychometric characteristics (Yalçın et al, 2022 ). The Turkish version of the CSS-12 revealed high internal consistency on the present data with Cronbach’s alphas ranging from 0.72 to 0.89.…”
Section: Methodsmentioning
confidence: 99%
“…Supporting these findings, Akbari et al ( 2021 ) converged a full mediation structural model in which relationship between COVID-19 and health anxiety was mediated by intolerance of uncertainty, emotional regulation capability and metacognitions, accounting for 71% of the unique variance of health anxiety. In a more recent national community survey conducted among a sample of 8,276 Turkish volunteers, Yalçın et al ( 2022 ) reported that perceived vulnerability to diseases significantly contributed to cyberchondria and indirectly predicted deterioration in sleep quality via cyberchondria.…”
Section: Introductionmentioning
confidence: 99%
“…The higher the score, the higher the severity of cyberchondria (McElroy et al., 2019 ). The CSS‐12 was adapted to Turkish by Yalçın, Boysan, Eşkisu, and Çam ( 2022 ) and yielded good validity and reliability with Cronbach's alphas ranging from 0.78 to 0.94. In the present study, The Turkish version of the CSS‐12 was found to have high internal consistency with Cronbach's alphas ranging from 0.71 to 0.87.…”
Section: Methodsmentioning
confidence: 99%
“…These trends worsened during the COVID-19 pandemic, triggering an increase in health anxiety and a search for information about a mysterious and frightening infection (17). Persons with a high fear of pandemic often search the Internet for information about COVID-19 disease, so fear of COVID-19 was closely associated with cyberchondria (18)(19)(20).…”
Section: Fear Of Covid- Cyberchondria and Preventive Behaviormentioning
confidence: 99%